(untitled) (Socio-economic relations in the digital society, 2019)
The essence and types of heuristic analysis of economic activity. Identify their strengths and weaknesses. The basic stages of business analysis using heuristic methods. Analyzed the essence of psychological management methods as the activation measures system performance workforce. We select the most eff ective heuristic methods allowing for the transformation of production processes. Attention is paid to the effectiveness of a special intra-process management practices and individual personal behavior. Effective management requires a co mbination and the use of the totality of methods of infl uence on the formation and development of individuals and the collective. Of particular importance are heuristic methods of management, so consider their essence and specificity.